Recalcamento e sistematização da escrita escolar - Bonfanti, Virgínia da Silva Camargo (2019)
I present a research about the acquisition of writing in a school environment based on the theoretical conceptions of language and subject as formulated by Psychoanalysis, especially in the works of Freud, Lacan and Pommier. I begin with a question to the graphophonic system that, because supposing that writing reproduces orality, writing is reduced to a technique whose assimilation depends on the development of motor skills. We realize, as teachers who deal with children of literacy age, that the distress experienced by most students when asked to write is not only linked to immature motor skills, as they are able to perform other motor activities that require more skill. than putting letter-like strokes together. What then would be at stake in the affliction that usually afflicts schoolchildren? In reflecting on this question, I could come up with another formulation: not only children, but also youth and adults who master the technique of writing, show suffering in front of a blank sheet of paper or a computer screen. This finding, also supported by theoretical readings in the field of psychoanalysis, led me to want to better understand the psychic events that are implicated in the act of writing. According to our observations, one of these events is linked to repression, one of the psychic operations that defines the way the subject confronts culture and stands before the principle of pleasure and reality. The objective of this research was to elaborate hypotheses about the writing of the elementary school students, following the repression action in their textual productions, considering the moment of appearance and disappearance of traces and drawings that are not under the symbolic order of the writing. standard taught at school and at the same time the installation of signifiers under the symbolic pact. By observing how the movement of writing acquisition occurs in the school, I was able to experience with students and their texts, ways in which movement towards writing occurs, this observation is only possible from the reactions presented by the children at the moment when Writing activities are requested, what we see appearing are manifestations ranging from standing still looking at the blank sheet of paper, to the situation of writing and then tearing the sheet so that the Other does not see what was written. There is no way to measure or say that psychic operations are being performed at that very moment, which we suppose is like the presence of a subject in the construction of the signifier who, despite the stumbling blocks, marks of his uniqueness is captured by language. This research was conducted as an educational product for the Professional Master's Degree Program in Basic Education Teaching at the Federal University of Goiás. (PPGEEB-CEPAE-UFG) 2017 to 2019.